Forensic Monitoring Project Report: Drina River and Gornji Džestje, Goražde - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Simmons, Tal Forensic Pathologists from the Tuzla Clinical Center and members of the Goražde Police exhumed three sites along the Drina River and in Gornji Džestje from 26-29 August 1997. Four bodies were recovered from the Drina River sites while a minimum of two were recovered from Gornji Džestje. Place of Exhumation: Goražde, Gornji Džestje, Vitkovići Date of Exhumation: 26-29 August 1997 Minimum Number of Exhumed Individuals: 006